Peningkatan Hasil Belajar IPA Dengan Menggunakan Metode Inkuiri - Tiurlan Tiurlan (JURNAL GLOBAL EDUKASI, 2018)
Abstract: The research aims to find out whether the method of inquiry can improve student learning outcomes in science subjects on the subject of Framework and Panca Indera Manusia in class IV SD Negeri 016528 BP. Mandoge academic year 2016/2017. The subject of this research is the fourth grade students of SD Negeri 016528 BP. Mandoge with 47 students. From pengelolahan data obtained the results of the average value obtained by students in the first cycle of 61.06. Of the 47 students, 30 students (63.83%) were completed in the study. Then on the second cycle there was an increase in the average value to 77.66. Of the 47 students, 40 students (85.11%) have experienced complete learning. Based on the increase of value starting from the initial test, cycle I and cycle II can be said that by using inquiry media can improve student learning outcomes in class IV Elementary School 016528 BP. Mandoge academic year 2016/2017 on science subjects subject of Framework and Five Senses of Human Beings. Keywords: inquiry, order, human senses Abstrak: Penelitian bertujuan untuk mengetahui apakah metode inkuiri dapat meningkatkan hasil belajar siswa pada mata pelajaran IPA pada pokok bahasan Rangka dan Panca Indera Manusia di kelas IV SD Negeri 016528 BP. Mandoge Tahun Pelajaran 2016/2017. Subjek penelitian ini adalah siswa kelas IV SD Negeri 016528 BP. Mandoge dengan jumlah siswa 47 orang. Dari pengelolahan data diperoleh hasil nilai rata-rata yang diperoleh siswa pada siklus I sebesar 61,06. Dari 47 siswa, 30 orang siswa (63,83%) telah tuntas dalam belajar. Kemudian pada siklus II terjadi peningkatan nilai rata-rata menjadi 77,66. Dari 47 orang siswa, 40 orang siswa (85,11%) telah mengalami ketuntasan belajar. Berdasarkan peningkatan nilai mulai dari tes awal, siklus I dan siklus II dapat dikatakan bahwa dengan menggunakan media inkuiri dapat meningkatkan hasil belajar siswa di kelas IV SD Negeri 016528 BP. Mandoge Tahun Pelajaran 2016/2017 pada mata pelajaran IPA pokok bahasan Rangka dan Panca Indera Manusia. Kata kunci: inkuiri, rangka, indera manusia